STRUCTURE AND FLORISTICS OF THE ARBOREAL COMPONENT OF A DYSTROPHIC CERRADÃO AND COMPARISON WITH OTHER CERRADÕES IN CENTRAL BRAZIL - Araújo, G. M.; Nascimento, A. R. T.; Lopes, S. F.; Rodrigues, R. F.; Ratter, J. A. (Edinburgh Journal of Botany, 2011)
This study describes the structure of the arboreal plant community in a cerradão fragment located at the Serra de Caldas Novas State Park, Goiás, central Brazil. It also compares the collected data with information from 10 other cerradão sites on dystrophic and mesotrophic soils. All trees of 4.77 cm or more diameter at breast height, in twenty-five 20 m × 20 m plots, were surveyed. Soil samples were analysed to determine the availability of nutrients. The vegetation had a discontinuous canopy, with a high density of small and medium-sized trees, and the soil was classified as dystrophic according to nutrient availability. Under ordination using Detrended Correspondence Analysis, species characteristic of the study site, such as Sclerolobium paniculatum and Emmotum nitens, were positioned in the central portion, while cosmopolitan species formed distinct groups, separated along the two axes. The community showed a low level of similarity in comparison to cerradões reported in the literature in other parts of Brazil, having more than 50% similarity only with three geographically close sites.
Keywords: Dystrophic cerradão; floristic survey; mesotrophic cerradão; multivariate analysis